2023
DOI: 10.1002/ajp.23484
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient balancing in a fruit‐specialist primate, the black‐and‐white ruffed lemur (Varecia variegata)

Abstract: Animals' foraging behavior and dietary choices are, in part, driven by their ultimate function: to meet nutritional demands. However, depending on their degree of dietary specialization and the availability and distribution of food resources in their environment, species may utilize different nutritional strategies. With shifting plant phenology, increasing unpredictability of fruiting, and declining food quality in response to anthropogenic climate change, existing nutritional constraints may become exacerbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 99 publications
(215 reference statements)
0
5
0
Order By: Relevance
“…The AP : NPE ratio in the diets of wild diademed sifaka lemurs (Propithecus diadema) remained remarkably constant across seasons and habitats (intact versus disturbed), suggesting macronutrient balancing [43]. Beeby et al [44] inferred nutrient balancing in another lemur, the black-and-white ruffed lemur (Varecia variegata), whose diet varied in AP : NPE across seasons but, as the authors had predicted, across the year the AP : NPE was maintained more tightly. Johnson et al [45] reported that guerezas (Colobus guereza) maintained a consistent AP : NPE when feeding across foraging patches, and the ratio was a good indicator of time spent foraging within patches.…”
Section: (A) Laboratory Experimentsmentioning
confidence: 93%
See 2 more Smart Citations
“…The AP : NPE ratio in the diets of wild diademed sifaka lemurs (Propithecus diadema) remained remarkably constant across seasons and habitats (intact versus disturbed), suggesting macronutrient balancing [43]. Beeby et al [44] inferred nutrient balancing in another lemur, the black-and-white ruffed lemur (Varecia variegata), whose diet varied in AP : NPE across seasons but, as the authors had predicted, across the year the AP : NPE was maintained more tightly. Johnson et al [45] reported that guerezas (Colobus guereza) maintained a consistent AP : NPE when feeding across foraging patches, and the ratio was a good indicator of time spent foraging within patches.…”
Section: (A) Laboratory Experimentsmentioning
confidence: 93%
“…Beeby et al . [44] inferred nutrient balancing in another lemur, the black-and-white ruffed lemur ( Varecia variegata ), whose diet varied in AP : NPE across seasons but, as the authors had predicted, across the year the AP : NPE was maintained more tightly. Johnson et al .…”
Section: Nutrient Balancing In the Laboratory And Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of non-human primates, for example, maintain daily protein intakes within narrow limits, allowing fat and carbohydrate to vary more widely with ecologically imposed variation in the macronutrient ratios of available diets—a pattern of macronutrient regulation termed ‘protein prioritization’ ( figure 1 a , b ). Known instances include spider monkeys [ 19 ], black howler monkeys [ 20 ], golden snub-nosed monkeys [ 17 ] ( figure 1 d ), Kenyan blue monkeys [ 18 ] ( figure 1 d ), black-and-white ruffed lemurs [ 21 ], orangutans [ 22 ] and chimpanzees [ 23 ].
Figure 1 Theoretical depiction of the protein prioritization pattern of macronutrient regulation and empirical examples from non-human primates.
…”
Section: The Power Of Proteinmentioning
confidence: 99%
“…Several studies have shown the behavioral impacts of seasonal resource availability on these lemurs (Balko, 1998;Balko & Brian Underwood, 2005;Beeby & Baden, 2021;Britt, 2000;Ratsimbazafy, 2002Ratsimbazafy, , 2006Rigamonti, 1993); fewer have investigated the physiological impacts of this seasonality (Morland, 1993;Vasey, 2004Vasey, , 2005. Due to their adaptations to frugivory, in combination with declines in calorie intakes during fruit-lean seasons (Beeby et al, 2023), ruffed lemurs may be at high risk of experiencing negative energy balance (expending more energy than they consume) during sustained periods of fruit scarcity. Moreover, the ability to maintain energetic conditions throughout lean seasons may be a driver of certain ruffed lemur life history traits, such as their "boom-bust" reproduction (Ratsimbazafy, 2002) and communal nesting (Baden, 2011;Baden et al, 2013).…”
mentioning
confidence: 99%